Objective and Subjective Sleep Disorders in Automated Peritoneal Dialysis. Issue 1 (17th February 2016) - Roumelioti, Maria-Eleni; Argyropoulos, Christos; Pankratz, Vernon Shane; Jhamb, Manisha; Bender, Filitsa H.; Buysse, Daniel J.; Strollo, Patrick; Unruh, Mark L.
Background: Automated peritoneal dialysis (APD) is one of the fastest growing dialysis modalities. It is unknown whether sleep and mood are disturbed while performing repeated overnight exchanges. Objectives: In this report, we aim to describe and compare the prevalence of sleep-disordered breathing (SDB), periodic limb movements (PLMS), poor sleep quality (SQ), and depression among APD patients compared with stages 3b–5 (estimated glomerular filtration rate ≤44 ml/min/1.73 m2) chronic kidney disease (CKD) and hemodialysis (HD) patients. Design: This is a cross-sectional, descriptive study. Setting: Study participants were recruited from outpatient nephrology clinics, local dialysis centers, and the Thomas E. Starzl Transplant Institute in Western Pennsylvania between April 2004 and July 2009. Patients: There were 186 participants in this study including 22 APD patients, 89 CKD patients, and 75 HD patients. Measurements: In-home polysomnography was performed and two questionnaires were completed, the Pittsburgh Sleep Quality Index (PSQI) and the Patient Health Questionnaire-9 (PHQ-9). Methods: SDB and PLMS were quantified by in-home unattended polysomnography; poor SQ was defined by a score >5 on the PSQI, and the presence of moderate to severe depression was defined by a score >5 on the PHQ-9. Results: The APD patients had a median age of 37.5 years, were predominantly female (72.7 %), and had a median body mass index (BMI) of 23.8 kg/m2. In univariate analyses, APD patients had significantly lower apnea-hypopnea index compared to HD patients by 12.2 points (likelihood ratio test p = 0.008) and revealed the least percent of TST with nocturnal hypoxemia compared to CKD patients by 2.7 points, respectively (likelihood ratio test p = 0.01). The APD group had also significantly greater stages 3 to 4 sleep compared to the CKD patients by 8.6 points (likelihood ratio test p = 0.009). In multivariate analyses and after adjustment for age, gender, race, and BMI, both APD and HD patients had higher average PSQI scores than CKD patients by 2.54 and 2.22 points, respectively (likelihood ratio test p = 0.005). No other comparisons of sleep parameters among groups reached statistical significance. Limitations: The limitations of this study are the small sample size of the APD population and the demographic and clinical differences among the three study groups. Conclusions: Despite differences in univariate analyses, after multivariate adjustment, APD patients had similar sleep parameters and sleep architecture and as poor SQ and symptoms of depression as HD patients. Future studies with larger APD cohorts are needed.